Comparison of Voluntary Feed Intake and Venom Production of Wild and Laboratory Bred Sand Vipers - Georgescu, Bogdan; Sălăjan, Gheorghe; Mierliţă, Daniel; Iozon, Doina; Odagiu, Antonia (Acta Agraria Debreceniensis, 2001)
The study was performed on vipers of the Vipera ammodytes ammodytes species and aimed to establish the differences in voluntary feed intake and venom production between a group of wild, recently captured vipers and a group of born and bred captive vipers. In addition, the influence of sex on both parameters was established. The research brought evidence of important differences concerning voluntary food ingestion and venom production between the two groups of animals. However, sex appeared not to significantly influence these parameters, both in wild, recently captured vipers and in born and bred captive vipers. Wild animals rapidly accommodated to the microclimate conditions in captivity and readily accepted food.